Indisciplina ou violência? As marcas nas escolas de Arapongas e Apucarana-PR - Marques, Maria de Fátima (2014)
This research is based on data collected in three Schools State Schools of Apucarana an three Schools State Schools Arapongas and aimed to present the natures of school violence that permeates everyday school life and to check whether that violence is correlated to the territory in which the school is located. We adopted a restricted conception of violence, seeking to escape the hyper conceptual expansion. The desire to limit school violence to acts of violence and especially the categories well marked by the Criminal Code does not have the power to underestimate the other facts that fall within the offenses and incivilities, but to characterize the acts and facts within the category may, in essence, establish a representation of what actually happens in schools and what is called school violence. We can see here the opportunity to overcome jargon as "the School is violent" since there is a certain relativism that point of view. One aim, by collecting data in school records, the nature of social acts registered by the school as occurrences that affect a negative factor in school routine. The research is a qualitative approach authoritative but even so it didn't exempt the quantitative data collection in schools, in the records of occurrences, which serve as reference for qualitative analysis. The temporal design to collect data in the records of occurrences of state schools is five years, from 2008 to 2012. In the data collected in the records occurrences of schools, there is widespread indiscipline. The pipelines prevalent are transgressions and incivilities. These behaviors repeated daily and combined with a lower number of criminal conducts composes a scene of violence.